THU0192 Evaluating Pharmacokinetic Predictors of Tofacitinib Clinical Response in Rheumatoid Arthritis. (15th July 2016) - Lamba, M.; Furst, D.; Dikranian, A.; Dowty, M.; Hutmacher, M.; Conrado, D.; Stock, T.; Nduaka, C.; Krishnaswami, S.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). A extended-release (XR) formulation to provide a once-daily (QD) dosing alternative to the available 5 mg twice daily (BID) immediate-release (IR) formulation has been developed. 1 Objectives: To determine the most relevant pharmacokinetic (PK) parameter driving the clinical response of tofacitinib to inform clinical development of the MR formulation. Methods: Clinical efficacy data (Disease Activity Score [DAS] and ACR 20/50/70 responses) from 5 Phase 2 RA dose-ranging studies of IR 1–30 mg BID and IR 20 mg QD across ∼1500 patients were analysed. Dose- and exposure-response (E-R) models were developed to characterise the time course of changes in DAS, including quantifying the delay between concentration and response, and to compare the predictive abilities of various PK parameters (total drug exposure as measured by area under the concentration-time profile [AUC], and peak [Cmax ] and minimum [Cmin ] plasma concentrations). Non-clinical efficacy data from a dose-fractionation study of multiple IR QD and BID doses using the murine collagen-induced arthritis (mCIA) model were also analysed to delineate the predictive ability of PK parameters. The relationship between tofacitinib exposure metrics and incidence of safety outcomes was explored using linear logistic models. Results: The E-R model yielded an equilibration half-life of 3.2 weeks for changes in DAS, substantially longer than the PK half-life of tofacitinib (∼3 hours). Application of this model to plasma PK profiles of MR and IR yielded superimposable predicted effective concentrations for both regimens (Fig 1 ). In a dose-ranging Phase 2 study, analyses of the IR 20 mg QD dose (similar AUC to the IR 10 mg BID dose, but 86% lower Cmin and ∼2-fold higher Cmax ) demonstrated similar efficacy to the IR 10 mg BID dose. DAS mean (standard error) change from baseline was -1.72 (0.14) for IR 20 mg QD vs -1.82 (0.15) for IR 10 mg BID; ACR 20/50/70 rates were 56/36/24% for IR 20 mg QD vs 58/28/12% for IR 10 mg BID at Week 12. Statistical comparison of PK parameters favoured AUC as a better predictor (p<0.05) of DAS changes than Cmax or Cmin, with little added value of Cmax or Cmin . In the mCIA model, BID and IR QD E-R curves were well aligned for AUC as the predictor, as demonstrated by concordance of concentrations producing 50% of maximum response. Comparing the predictive ability of AUC, Cmax and Cmin for safety events of interest (eg serious infections) also supported AUC as the most relevant PK parameter (data not shown). Conclusions: These analyses support AUC as the relevant predictor of tofacitinib clinical response and inform clinical development of an MR formulation of tofacitinib for QD dosing. References: Lamba M et al. Ann Rheum Dis 2015; 74 (Suppl 2): 626. Acknowledgement: Previously presented (Lamba M et al. Arthritis Rheumatol 2015; 67 (S10): 2755) and reproduced with permission from Arthritis Rheumatol. This study was funded by Pfizer Inc. Editorial support was provided by S Johnson of Complete Medical Communications, and funded by Pfizer Inc. Disclosure of Interest: M. Lamba Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Furst Consultant for: Pfizer Inc, A. Dikranian Consultant for: Pfizer Inc and AbbeVie, Speakers bureau: Pfizer Inc and AbbeVie, M. Dowty Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Hutmacher Consultant for: Pfizer Inc, D. Conrado Employee of: Pfizer Inc, T. Stock Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Nduaka Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Krishnaswami Shareholder of: Pfizer Inc, Employee of: Pfizer Inc